The Relationship between Molecular Structure and Foaming of Poly(ethylene glycol)—Poly(propylene glycol) Triblock Surfactants in Cementitious Materials - Mohammad Sadegh Tale Masoule; Ali Ghahremaninezhad (Buildings, 2024)
This study investigates the relationship between the molecular structure and foaming of poly(ethylene glycol) and poly(propylene glycol) triblock copolymers in Portland cement pastes. Four copolymers with different molecular structures were studied at varying concentrations. All copolymers showed a reduction in surface tension of the cement pore solution; however, only some of them demonstrated foaming and air entraining in cement paste. The results indicated that the molecular structure parameter, hydrophilic-to-lipophilic balance (HLB), has a direct relationship with the foaming and air-entraining performance of the copolymers. The total organic carbon measurements showed very small adsorption of these non-ionic copolymers on hydrating cement particles due to the lack of surface charge needed to interact with the heterogeneously charged surface of hydrating cement. In addition, these copolymers did not seem to affect the flow of cement paste due to a lack of adsorption on cement particles. The cement paste modified with the copolymers showed increased water sorption compared to the control paste due to the increased capillary porosity and slight increase in pore surface hydrophilicity. However, the freeze-thaw resistance was shown to improve with an increase in the number of air voids in the modified cement pastes. The findings establish the relationship between molecular properties of copolymers and their air-entraining performance in cement paste to mitigate the damages caused by freeze-thaw action.